Citation frequency and the value of patented innovation - Dietmar Harhoff; Francis Narin; Frederic M. Scherer; Katrinl Vopel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
Through a survey, economic value estimates were obtained on 962 inventions made in the United States and Germany and on which German patent renewal fees were paid to full-term expiration in 1995. A search of subsequent U.S. and German patents yielded a count of citations to those patents. Patents renewed to full term were significantly more valuable than patents allowed to expire before their full term. The higher an invention's economic value estimate was, the more the relevant patent was subsequently cited. results from two wide-ranging surveys, one in Germany and one in the United States, support Trajtenberg's conclusion that patents with greater economic value are more heavily cited in subsequent patents. Our evidence suggests at least a two-stage escalation of economic values and citation counts. First, patents that are renewed to full term expiration in environments such as Germany with highly progressive annual maintenance fees are more valuable and more highly cited than run-of-the-mill patents allowed to expire before running to full term. Second, within the relatively exclusive cohort of fullterm patents, citation frequency rises with economic value, although with considerable noise in the relationship. The most cited patents turn out to be very valuable indeed, with a single U.S. citation implying on average more than 1 million of economic value. These findings provide new support for research seeking to overcome the limitations of simple patent counts as a measure of innovative contribution by acquiring data on citation frequencies and the number of nations in which patent protection is sought. – – Durch eine Unternehmensbefragung wurde der Wert von 962 Patenten von US-amerikanischen und deutschen Anmeldern ermittelt, die den Patentschutz durch Zahlung der Verlängerungsgebühren von 1977 bis 1995 in Deutschland aufrechterhalten hatten. Außerdem wurde für diese Patente die Zahl der Zitationen (Bezugnahmen in späteren Patenten) ermittelt. Die bis zur gesetzlichen Laufzeit aufrechterhaltenen Patente wiesen eine signifikant höhere Zahl von Zitationen auf als Patente, die nicht verlängert worden waren. Zwischen der Zahl der Zitationen und dem Wert eines Patentes gibt es einen statistisch signifikanten Zusammenhang, der in dieser Studie näher beschrieben wird.
Keywords: 330